2018
DOI: 10.18239/ocnos_2018.17.1.1278
|View full text |Cite
|
Sign up to set email alerts
|

Explorando la relación entre fluidez lectora y competencia lectora en Educación Secundaria

Abstract: Un nivel adecuado de competencia lectora es esencial para ejercer los derechos fundamentales en la sociedad de la información hiperconectada del siglo XXI. La fluidez lectora es uno de los componentes que influye en la comprensión lectora. En este artículo se explora la relación entre la fluidez lectora y la competencia lectora, además de que aporta un instrumento confiable para su medición en el nivel secundario. La investigación es descriptiva–correlacional. La muestra estuvo compuesta por 382 estudiantes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…For the authors [42], reading literacy is vital for the exercise of citizens' rights in today's society by being able to access, understand and reflect on information, as well as for the economic growth of different countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the authors [42], reading literacy is vital for the exercise of citizens' rights in today's society by being able to access, understand and reflect on information, as well as for the economic growth of different countries.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are multiple factors that can improve reading proficiency. [42] argue that fluency and reading proficiency are positively related through mutual feedback where the level of reading comprehension facilitates fluency in essential aspects and reading comprehension in essential aspects facilitates comprehension of the text. [18] found that systematic phonics instruction leads to an improvement in both reading and writing skills.…”
Section: School Libraries and Their Evolutionmentioning
confidence: 99%
“…This skill unequivocally contributes to reading comprehension in children and adolescents [60,61]. However, reading fluency is not considered a strong predictor of reading comprehension [60,62,63]. This is due to the influence of numerous additional factors involved in reading comprehension, such as the content and characteristics of the text, or the syntactic, semantic, and pragmatic context in which the words or sentences are located [64].…”
Section: Definition Of Reading Skillsmentioning
confidence: 99%
“…Los hallazgos obtenidos deben de ser interpretados con cierta cautela, debido a que no pueden ser valorados en términos de causalidad. El rendimiento académico del alumnado no está solamente influenciado por la metodología docente, sino que influyen otros factores -contexto socio-económico, políticas educativas, centro escolar, factores asociados al estudiante, factores familiares y ambientales, desempeño y desarrollo docente, factores emocionales, factores tecnológicos, etcétera- (Amiama-Espaillat & Mayor-Ruiz, 2018;Gil et al, 2018;Gil-Flores & García-Gómez, 2017;Martínez-Oviedo, Toledo-Toledo & Martínez-Mendoza, 2021;Vázquez-Cano, De-la-Calle-Cabrera, Hervás-Gómez & López-Meneses, 2020).…”
Section: Discusión Y Conclusionesunclassified